Use of Low‐Density Lipoprotein–Lowering Therapies Before and After PCSK9 Inhibitor Initiation. Issue 9 (5th May 2020) - Rymer, Jennifer A.; Mues, Katherine E.; Monda, Keri L.; Bratton, Emily W.; Wirtz, Heidi S.; Okerson, Ted; Overman, Robert A.; Brookhart, M. Alan; Muntner, Paul; Wang, Tracy Y.
Abstract : Background: Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) are used to reduce low‐density lipoprotein (LDL) cholesterol. PCSK9i use after initiation, as well as persistence with or alterations to other LDL‐lowering therapy after PCSK9i initiation, is not well understood. Methods and Results: We conducted a retrospective study of alirocumab or evolocumab (PCSK9i) new users from July 2015 to December 2017 in the MarketScan Early View database of US commercial insurance beneficiaries. We determined the prevalence of PCSK9i interruption (≥30‐day gap in supply) and LDL‐lowering therapy use in the year after PCSK9i initiation. The average age of 6151 patients initiating PCSK9i therapy was 63 years, 44.4% were women, and 76.8% had atherosclerotic cardiovascular disease. Overall, 52.2% (95% CI, 50.8%–53.7%) of patients had an interruption in PCSK9i therapy in the first year after treatment initiation and 62.5% remained on PCSK9i therapy at 1‐year postinitiation. Also, 27.7% of patients were taking a statin at the time of PCSK9i initiation, with only 22.4% on statin therapy at 1 year after PCSK9i initiation. Ezetimibe use decreased from 20.9% at the time of PCSK9i initiation to 12.0% a year later. By 1 year after PCSK9i initiation, 44.0% of patients had experienced an interruption in all LDL‐lowering therapies, and 26.6% were no longer on any LDL‐lowering therapies. Conclusions: After PCSK9i initiation, statins were often discontinued, whereas more than half of patients experienced an interruption in PCSK9i therapy. These results suggest that many new PCSK9i users may remain at high risk for cardiovascular events because of interruptions in LDL‐lowering therapy.